2005
DOI: 10.1007/s10786-005-0057-3
|View full text |Cite
|
Sign up to set email alerts
|

Sources of High-Power Ultrawideband Radiation Pulses with a Single Antenna and a Multielement Array

Abstract: Sources of high-power ultrawideband electromagnetic pulses are described. They consist of a generator of single-polarity pulses, a bipolar pulse former, and a radiating system, for which either a single antenna or a 16-element antenna array is used. The values of the effective potential E p R = 440 kV for the single antenna and 1.7 MV for an array excited by a bipolar pulse with a duration of 2 ns and a repetition rate of 100 Hz are obtained. 1 2 3 4 Fig. 1. External view of source with an antenna array: ( 1 )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…As it follows from the data presented in Figure 9, a single CA (k = 0.26) (Gubanov et al, 2005) is significantly less effective than a 3.66 m diameter impulse radiating antenna (k = 0.5) (Giri et al, 1997). As it follows from the data presented in Figure 9, a single CA (k = 0.26) (Gubanov et al, 2005) is significantly less effective than a 3.66 m diameter impulse radiating antenna (k = 0.5) (Giri et al, 1997).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…As it follows from the data presented in Figure 9, a single CA (k = 0.26) (Gubanov et al, 2005) is significantly less effective than a 3.66 m diameter impulse radiating antenna (k = 0.5) (Giri et al, 1997). As it follows from the data presented in Figure 9, a single CA (k = 0.26) (Gubanov et al, 2005) is significantly less effective than a 3.66 m diameter impulse radiating antenna (k = 0.5) (Giri et al, 1997).…”
Section: Discussionmentioning
confidence: 60%
“…Previous researches (Gubanov et al, 2005;Efremov et al, 2011) have shown the validity of using this relation for estimation of the far-field zone boundary at excitation of the antenna arrays with bipolar pulses. For this purpose, we will use the relation for the harmonic signals r = 2D 2 /λ 0 , where λ 0 = τ p c, τ p is the length of a bipolar voltage pulse at the input of the feeder system, c is the velocity of light, D is the maximum transverse dimension of the antenna array.…”
Section: Radiation Of Ultrawideband Pulsesmentioning
confidence: 91%
“…When the transmitting antenna was excited by a monopolar voltage pulse (MP) of duration τ p = 3 ns at a 10% amplitude level, antenna KA 1 was used. Antennas KA 2, KA 3, and KA 4 were used when the excitation was performed, respectively, by a bipolar pulse (BP) with τ p = 2 ns, MP with τ p = 1 ns, and BP with τ p = 0.5 ns. To record the waveforms of the UWB pulses, an unbalanced TEM‐antenna with the ground plate having dimensions 1200 × 500 mm was used as a reference gage.…”
Section: Characteristics Of the Active Antennamentioning
confidence: 99%
“…(3) A relativistic backward-wave oscillator (BWO) excited at the TM 01 mode by a tubular electron beam, which is generated in a magnetically-insulated coaxial diode by a nanosecond electron accelerator using the "Sinus-160" high-voltage pulse oscillator [12] based on the resonance Tesla transformer (Institute of High-Current Electronics of the Siberian Branch of the Russian Academy of Sciences). The experimental device was operated in the single-pulse regime.…”
Section: Microwave Pulsementioning
confidence: 99%